The life and works of Vladimir Voinovich : the satirist as exile - Farmer, Rachel S. (1997)
This study undertakes an examination of the life and works of the satirist Vladimir Voinovich, set in the context of satire in general, and in particular against the changing political, ideological and artistic background of the Soviet Union and the new Russia. It is demonstrated that in certain respects he is typical of his generation and in others an exception.